Casa Barrio José: a narrative environment in the (dis)composition of an installation (Praxis Educativa, 2024)
The decompositions of the installation Casa Barrio José, in this text, ponder a narrative environment that acts as a de-local-ization of a neighborhood in Mar del Plata (Argentina). In imbrication with narrative, autobiographical and performative research in education, a domestic, everyday and close queer theory is named from it. It initially sought to point out the corruption reproduced in the naming of public space, and then expanded as a house-laboratory. In it, residencies and volunteering led to the sharing of a recognition program for domestic and environmental artist-educator-researchers in nineteen performances, entitled Doctor Honoris Casa. As an epistemic embodiment and beyond its materiality, this inquiry does not position a conscious or voluntarist subject or a neutral and deliverable object, much less an experiment or an experience. Its continuity is in the relationship, in being research. A theoretical exercise and a way of producing knowledge that is inscribed as a life-research in the body-home that inhabits us.
Keywords: autobiography; Narrative research; installation; performativity; Queer theory